Lycopene improves on basic hematological and immunological parameters in diabetes mellitus - Ejike, Daniel Eze; Adam, Moyosore Afodun; Josephine, Kasolo; Keneth Iceland, Kasozi (BMC Research Notes, 2023)
Objective: Diabetes is associated with an upset of hematological and immunological parameters in humans, how- ever information on the effects of Lycopene is scarce. The aim of the study was to gain information on basic changes in hematological parameters as markers for safety since anemia as a complication in diabetic chemotherapy has been reported. Results: Lycopene had anti-anemic effects and improved on the immune status of diabetic rats and these obser- vations were dose independent. There was a decrease in neutrophil, low neutrophil–lymphocyte ratio and platelet counts and stable albumin, globulin levels. Lycopene could exert its protective effects through a balance of basic hematological physiological variables.